Hamster activity and estrous cycles: control by a single versus multiple circadian oscillator(s). - Carmichael, M S (1981)
Running activity onset and estrous onset were recorded for hamsters exposed to progressively shorter daily light/dark (T) cycles. The period of the estrous cycle was a quadruple multiple of the period of the activity rhythm during entrainment to T cycles of 23.5-21.5 hr. There was no evidence of desynchronization of the activity and estrus rhythms. The very short estrous periods shown during exposure to short T cycles indicate that an intrinsic 96-hr interval for ovarian follicular maturation does not determine the period of the estrous cycle. Dissociation of estrous and running activity onsets occurred for all hamsters: estrous onset generally preceded running activity onset for T greater than or equal to 23.0 hr; for shorter T cycles, estrous onset generally lagged behind running activity onset. Wheel-running activity was intermittently split into entrained and free-running components for one female: at T = 22.0 hr, estrous onset was coupled first with one and then with the other of the split activity components. These findings suggest that two or more separate circadian oscillators may control timing of the activity and estrous rhythms.